VERBA BERPELENGKAP DALAM BAHASA INDONESIA SUATU KAJIAN STRUKTUR DAN SEMANTIK - Eni Karlieni (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2005)
This research study attempts to describe morphological forms of verbs withcomplements in Indonesian and their syntactic and semantic characteristics.The method employed in this study was the descriptive one, which wassynchronically applied. The data sources were Indonesian textbooks for elementaryschools, junior high schools, and senior high schools, besides newspapers such asKompas, Republika and Pikiran Rakyat.Morphologically, verbs with complements can be free verb bases, derived verbs,and reduplicated verbs. On the basis of their syntactic characteristics, the verbs canbe those with noun complements (noun phrases), verbals (verbal phrases), adjectives(adjectival phrases), adverbials (adverbial phrases), and numbers (numeral phrases).On the basis of their semantic characteristics, the verbs can be classified into punctualverbs, dynamic verbs, and static verbs.Keywords: argument, complement, constituent